Evaluating the quality of colorectal cancer care across the interface of healthcare sectors - Ludt, Sabine; Urban, Elisabeth; Eckardt, Jörg; Wache, Stefanie; Broge, Björn; Kaufmann-Kolle, Petra; Heller, Günther; Miksch, Antje; Glassen, Katharina; Krug, Katja; Bölter, Regine; Ose, Dominik; et al. (PLOS ONE, 2013)
Background Colorectal cancer (CRC) has a high prevalence in western countries. Diagnosis and treatment of CRC is complex and requires multidisciplinary collaboration across the interface of health care sectors. In Germany, a new nationwide established program aims to provide quality information of healthcare delivery across different sectors. Within this context, this study describes the development of a set of quality indicators charting the whole pathway of CRC-care including data specifications that are necessary to operationalize these indicators before practice testing. Methods Indicators were developed following a systematic 10 step modified ‘RAND/UCLA Appropriateness Method’ which involved a multidisciplinary panel of thirteen participants. For each indicator in the final set, data specifications relating to sources of quality information, data collection procedures, analysis and feedback were described. Results The final indicator set included 52 indicators covering diagnostic procedures (11 indicators), therapeutic management (28 indicators) and follow-up (6 indicators). In addition, 7 indicators represented patient perspectives. Primary surgical tumor resection and pre-operative radiation (rectum carcinoma only) were perceived as most useful tracer procedures initiating quality data collection. To assess the quality of CRC care across sectors, various data sources were identified: medical records, administrative inpatient and outpatient data, sickness-funds billing code systems and patient survey. Conclusion In Germany, a set of 52 quality indicators, covering necessary aspects across the interfaces and pathways relevant to CRC-care has been developed. Combining different sectors and sources of health care in quality assessment is an innovative and challenging approach but reflects better the reality of the patient pathway and experience of CRC-care.
Gesehen am 08.06.2021